Literasi Keuangan yang Inklusif dan Digitalisasi Payment (QRIS) Bagi Home Industry Kerajinan Songkok Resam di Desa Sengir - Ifada, Zuriyat; Juliansyah, Ari; Rais, Zalva Rosemayini Putri; Hildky, Kanaya Ramadhani (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
Financial literacy skills are crucial for micro-entrepreneurs to sustainably manage and develop their businesses. Financial literacy encompasses the ability to manage income and expenses, record financial records, save, invest, and make sound financial decisions. Low levels of financial literacy and limited use of digital Payment systems are also still found among small business owners in the Bangka Belitung Islands Province, including the songkok resam artisans in Sengir Village. This Community Service activity was conducted in Sengir Village, Payung District, South Bangka Regency, Bangka Belitung Islands Province, from November to December 2025. The method used was a participatory approach that emphasized active community involvement in every stage of the activity. From the results and discussion, it can be concluded that increasing financial literacy and the implementation of QRIS-based Payment digitalization have had a positive impact on songkok resam artisans in Sengir Village. Indicators of success include increased knowledge of artisans regarding business financial management, the ability to perform simple record keeping, and the number of participants who successfully own and use QRIS in transactions.